Driving and sustaining trauma-informed organizational change: The role of healthcare leadership - Amidu Alhassan; Sana Rasheed; Ahmed Asad Raza; Bushra Murtaza; Azka Mujeeb; Ayesha Iqbal Mansoor (Health Sciences Review, 2025)
Trauma is a major public health concern, both omnipresent and burdensome. Trauma-informed care [TIC] is regarded as a multilevel approach that alters the way organizations perceive and address trauma. TIC has shown a beneficial impact on patient health, employee well-being, and institutional performance. Efforts to implement TIC necessitate leadership backing and the establishment of policies to guarantee consistent application. This review examines the implementation and sustainability of TIC in healthcare, focusing on its principles, role of leadership, challenges, and strategies. It aims to provide insights to enhance patient outcomes, support staff well-being, and foster a trauma-informed healthcare culture. TIC is a well-established framework for supporting trauma survivors and improving outcomes in emergency departments. Studies have shown that implementing TIC education programs can reduce the number of patients subjected to physical restraints and the overall time spent in restraints. Strategic leaders must develop standardized policies to guide the change process. Staff trained under certified programs provide better results in trauma-informed healthcare by influencing their knowledge, behavior, and beliefs. Organizational challenges include the need for repeated training and ongoing support. Community clinics face time constraints in consultations, financial constraints, and high patient turnover. Sustaining trauma-informed change requires systemic strategies that prioritize safety, empowerment, and collaboration. Supportive leadership empowers employees through shared decision-making and continuous training. Embedding TIC into organizational policies ensures sustainability by promoting safety, equity, and inclusivity. Future research should evaluate and refine TIC practices to build a stronger evidence base.